Direct Comparison of Fixed Flexion Radiography and MRI in Knee Osteoarthritis: Responsiveness Data from the Osteoarthritis Initiative - Wirth, Wolfgang (2012)
OBJECTIVE: Minimum radiographic joint space width (mJSW) represents the FDA standard for demonstrating structural therapeutic benefits for knee osteoarthritis (KOA), but only shows moderate responsiveness (sensitivity to change). We directly compare the responsiveness of MRI-based cartilage thickness and JSW measures from fixed-flexion radiography (FFR) and explore the correlation of region-matched changes between both methods. METHODS: 967 knees of Osteoarthritis Initiative participants with radiographic KOA were studied: 445 over one year with coronal FLASH MRI and FFR, and 375/522 over one/two years with sagittal DESS MRI and FFR. Standardized response means (SRM) of cartilage thickness and mJSW were compared using the sign-test. RESULTS: With FLASH MRI, SRM was −0.28 for medial compartment (MFTC) cartilage loss vs. −0.15 for mJSW, and −0.32 vs. −0.22 for the most sensitive MRI subregion (central MFTC) vs. the most sensitive fixed location JSW(X=0.25). With DESS MRI, one-year SRM was −0.34 for MFTC vs. −0.22 for mJSW and −0.44 vs. −0.28 for central MFTC vs. JSW(X=0.225). Over two years, the SRM was significantly greater for MFTC than for mJSW (−0.43 vs. −0.31, p=0.017) and for central MFTC than for JSW(X=0.225) (−0.51 vs. −0.44, p<0.001). Correlations between changes in spatially matched MRI subregions and fixed location JSW were not consistently higher (r=0.10–0.51) than those between non-matched locations (r=0.15–0.50). CONCLUSIONS: MRI displays greater responsiveness in KOA than JSW FFR-based JSW, with the greatest SRM observed in the central medial femorotibial compartment. Fixed-location radiographic measures appear not capable of determining the spatial distribution of femorotibial cartilage loss.